Tocolytic effect of parecoxib, a new parenteral cyclo-oxygenase-2-specific inhibitor, on the spontaneous and prostaglandin-induced contractions of rat isolated myometrium - Ayar, A. (Wiley, 2007)
1. The present study was undertaken to elucidate the effects of parecoxib, a novel cyclo-oxygenase (COX)-2 inhibitor, on spontaneous and prostaglandin-induced contractions of uterine smooth muscle. 2. Non-pregnant adult Wistar rats were decapitated and dissected to isolate myometrial strips. The tissue was mounted in 5 mL organ baths filled with Krebs' solution that was maintained at 37 degrees C and bubbled continuously with a mixture of 95% O-2-5% CO2 to give pH 7.4. Contractions were recorded through transducers for isometric tension recording. The dose-dependent effects of parecoxib on contractility were quantified by changes in the mean amplitude, frequency and area under the contractile curve (AUC; percentage of control conditions) of the isometric tension recordings, averaged over 5 min intervals. Statistical analyses were performed using ANOVA. 3. Application of parecoxib (50-900 mu mol/L) caused dose-dependent decreases in mean amplitude, mean frequency and mean AUC of both spontaneous and prostaglandin-induced contractions. Mean percentage inhibition of the AUC of spontaneous contractions was found to be 29, 56, 74 and 84% in the presence of 50, 150, 300 and 600 mu mol/L parecoxib, resepctively (n = 8). In the case of prostaglandin (PG) F-2 alpha-induced contractions, 100, 300, 600 and 900 mu mol/L parecoxib resulted in a 27, 43, 61 and 73% inhibition, respectively (n = 9). Moreover, pretreatment with parecoxib (600 mu mol/L) reduced the responsiveness and maximum contractility to PGF(2 alpha) compared with non-treated strips. 4. The data from the present study indicate, for the first time, that parecoxib inhibits spontaneous and prostaglandin-induced contractions of rat myometrium in vitro. These results raise the possibility that parecoxib may be of therapeutic use in the management of preterm labour and dysmenorrhoea.
Keywords: contractility; cyclo-oxygenase 2 inhibitors; myometrium; parecoxib; prostaglandin F-2 alpha; rat